2011
DOI: 10.3858/emm.2011.43.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidin extract ameliorates monosodium iodoacetate-induced osteoarthritis

Abstract: Abbreviations: GSPE, grape seed proanthocyanidin extract; MIA, monosodium iodoacetate; MMP, matrix metalloproteinase; O2 -, superoxide anion; OA, osteoarthritis; OH, hydroxyl radicals; ONOO -, peroxynitrite; PWL, paw withdrawal latency; PWT, paw withdrawal threshold; ROS, reactive oxygen species; TRP, transient receptor potential; VIP, vasoactive intestinal peptide Abstract Osteoarthritis (OA) is an age-related joint disease that is characterized by degeneration of articular cartilage and chronic pain. Oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 37 publications
2
55
2
Order By: Relevance
“…6). No significant lesions or abnormal staining were observed in any samples from the normal group 30,33 (Fig. 5).…”
Section: Histological Analysismentioning
confidence: 65%
“…6). No significant lesions or abnormal staining were observed in any samples from the normal group 30,33 (Fig. 5).…”
Section: Histological Analysismentioning
confidence: 65%
“…ROS play crucial roles in inhibiting cartilage matrix synthesis, inducing chondrocyte apoptosis, and breaking down the cartilage matrix. 29 The VT-SR, with abundant polyphenols, displayed significant antioxidative effects. Comparing the phytochemical contents and antioxidative effects, the VT-SR had significant free radicalscavenging activities due to its abundant total phenol and total flavone contents.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has indicated that grape seed proanthocyanidin extracts (GSPE) have secondary effects that may have a more direct antiinflammatory effects through modulation of immune cells. In rodents, GSPE reduced edema and local levels of IL-1β, TNFα, and PGE 2 following carrageenan, 62 pain in the late phase of the formalin test, 63 hyperalgesia and allodynia in an osteoarthritis model, 64 hypersensitivity and TNFα levels in an arthritis model, 65 and allodynia in a streptozotocin-induced diabetic neuropathy model. 65a Additionally, in a model of temporomandibular joint pain via complete Freund's adjuvant, GSPE reduced microglia and astrocyte activation in the brain and nerves in addition to a local reduction of MAPK, 66 suggesting an immune-cell-specific mechanism of action.…”
Section: Grape Seed Extractmentioning
confidence: 99%